1989
DOI: 10.1080/0260747890150103
|View full text |Cite
|
Sign up to set email alerts
|

Reflective Teachers and Reflective Tutors: school experience in an initial teacher education course

Abstract: The newly developing four-year B.Ed. course of initial teacher education at Oxford Polytechnic is based on the development of a reflective teacher/tutor approach. School experience has been central to the development, because the approach requires that attention be paid to the perspectives of the three groups involved: teachers, tutors and students. The process of action research in which these perspectives were taken into account is described. The resulting simultaneous development of the model of reflective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The theory-practice gap is an important issue that has been discussed in many studies concerned with teacher education (e.g. Ashcroft and Griffiths 1989;Cheng, Cheng, and Tang 2010;Griffiths and Tann 1992;Smith and Hodson 2010). The pre-service teachers' comments on this issue can be summarised under two interrelated points: the difference between theory and practice, and putting theory into practice.…”
Section: Theory Versus Practicementioning
confidence: 98%
“…The theory-practice gap is an important issue that has been discussed in many studies concerned with teacher education (e.g. Ashcroft and Griffiths 1989;Cheng, Cheng, and Tang 2010;Griffiths and Tann 1992;Smith and Hodson 2010). The pre-service teachers' comments on this issue can be summarised under two interrelated points: the difference between theory and practice, and putting theory into practice.…”
Section: Theory Versus Practicementioning
confidence: 98%
“…Other studies show that student teachers feel there is a lack of 'connection' between the teacher education programme and the school-based teaching experiences (Hobson et al 2008, 414). It is very hard to preserve the unity of theory and practice during a short teaching practice period in schools (Ashcroft and Griffiths 1989). Zeichner and Tabachnick (1981) found that many newly learnt teaching theories or conceptions developed during teacher education programmes are 'diluted' by the initial confrontation during their teaching practice.…”
Section: The Gap Between the Theory And Practice Of Teachingmentioning
confidence: 99%
“…Ashcroft & Griffiths, 1989;Lucas, 1989) Canada, (e.g. Clandinin & Connelly, 1986;Mackinnon & Erickson, 1988), and other parts of the world.…”
Section: Introductionmentioning
confidence: 99%